The aggregate labor market effects of the Swedish Knowledge Lift program - James Albrecht; Gerard J. van den Berg; Susan Vroman (Institute for the Study of Labor (IZA), 2006)
The Swedish adult education program known as the Knowledge Lift (1997-2002) was unprecedented in its size and scope, aiming to raise the skill level of large numbers of low-skill workers. This paper evaluates the potential effects of this program on aggregate labor market outcomes. This is done by calibrating an equilibrium search model with heterogeneous worker skills using pre-program data and then forecasting the program impacts. We compare the forecasts to observed aggregate labor market outcomes after termination of the program.
urn:nbn:de:101:1-20090406121
Keywords: 330; Beschäftigungsgesellschaft; Qualifikation; Beschäftigungseffekt; Ökonometrisches Makromodell; Schweden